Prototipe Lemari Pakaian Pintar (Lappin) dengan Platform Mobile Web Application - Luthfi Kusuma; Andrian Rakhmatsyah; Sidik Prabowo (eProceedings of Engineering, 2018)
Abstrak User memiliki tiga kebutuhan pokok dalam menjalani kehidupan sehari-hari, yaitu pakaian (sandang), makanan (pangan), dan tempat tinggal (papan). Pada jurnal ini terdapat penjelasan tentang produk tugas akhir yang telah dibuat yaitu sebuah desain Lemari Pakaian Pintar (Lappin). Lappin memiliki tujuan utama yaitu membantu user melakukan monitoring pakaian yang tersimpan di dalamnya. Pakaian yang telah dipasangi Radio Frequency Identification (RFID) tag akan terdeteksi saat dimasukkan ke dalam Lappin. Kemudian data dikirimkan yang selanjutnya diterima oleh web server sekaligus melakukan update informasi pakaian yang ditampilkan pada website. Fitur utama dari Lappin adalah memunculkan notifikasi jika terdapat pakaian yang telah lama tidak dipakai dan pop up jika ada pakaian yang telah lebih lama disimpan daripada pakaian yang diambil. Mengaplikasikan RFID, konsep embedded system, web server, dan kemudahan akses online, diharapkan desain Lappin ini dapat menjadi solusi dari masalah pengaturan penyimpanan pakaian yang dimiliki. Kata Kunci : RFID, Embedded System, wardrobe, raspberry, wemos d1 r2  Abstract Basically, human has three type of needs in order to live the daily life to the fullest, which are clothes, feast, and shelter. In this journal, there have been written about an explanation of a final assignment’s product that called Smart E-Wardrobe (named Lappin). This wardrobe will be able to aid it’s user to monitor every clothes that have been stored in it. Clothes that already embedded with Radio Frequency Identification (RFID) tag will detected once put inside Lappin. Then data that have been sent, will be received by web server, in order to update clothes information that will be shown on the website. Main fiture of Lappin is to show notification on it’s website, in case there are clothes that has not been used for specifically long time and to create pop up notification that tell user if there are any older clothes that been stored inside Lappin. Based on application of RFID, embedded system concept, web server, and easiness of online access, hopefully this E-Wardrobe will become the solution to aid human’s need of clothes storage managing in purpose of less money spent in fashion and maximizing both effectiveness and efficiency of our stored clothes. Keywords : RFID, Embedded System, wardrobe, raspberry, wemos d1 r2